2015
DOI: 10.1515/ijfe-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Neural Network and Response Surface Methodology Performance on Fermentation Parameters Optimization of Bioconversion of Cashew Apple Juice to Gluconic Acid

Abstract: The study examined the impact and interactions of cashew apple juice (CAJ) concentration, pH, NaNO 3 concentration, inoculum size and time on gluconic acid (GA) production in a central composite design (CCD). The fermentation process and parameters involved were modeled and optimized using artificial neural network (ANN) and response surface methodology (RSM). The ANN model established the optimum levels as CAJ of 250 g/l, pH of 4.21, NaNO 3 of 1.51 g/l, inoculum size of 2.87% volume and time of 24.41 h with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Tesfaw and Assefa [46] also confirm the importance of the finding that lower inoculum size reduces the cost of production in ethanol fermentation. The mutually significant relationship between inoculum size and temperature was due to the use of a commercial strain (Anchor Instant Yeast) which operated within the specified temperature range (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • C) in the design of the experiment. …”
Section: Rsm Modeling Results For Ethanol Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tesfaw and Assefa [46] also confirm the importance of the finding that lower inoculum size reduces the cost of production in ethanol fermentation. The mutually significant relationship between inoculum size and temperature was due to the use of a commercial strain (Anchor Instant Yeast) which operated within the specified temperature range (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • C) in the design of the experiment. …”
Section: Rsm Modeling Results For Ethanol Productionmentioning
confidence: 99%
“…RSM quantifies the effect of the control variables, alone or in combination, on a selected response. In addition to analyzing the effects of the independent variables, this method also generates a mathematical expression that describes the relationship between variables and a selected response [25]. Pereira et al [22] used a Placket-Burman design to initially select the critical nutrients for CSL and other low-cost nutrients for ethanol fermentation, followed by a Box-Behnken design for the optimization of the selected nutrients [22].…”
Section: Glucose (G/l)mentioning
confidence: 99%
See 1 more Smart Citation
“…RSM defines the effect of the independent variables, alone or in combination, in the processes. In addition to analyzing the effects of the independent variables, this methodology also generates a mathematical model [23]. The applicability of RSM to optimization studies has been demonstrated successfully [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Neural Network (ANN), which is a computational method that can mimics the neurological processing capability of the human brain, has also been applied to modeling of many food processing studies. These studies include gluconic acid (Osunkanmibi, Olowlabi & Betiku, 2015), ethanol (Betiku & Taiwo, 2015) and oxalic acid (Emeko et al, 2015) production processes as well as in enzymatic reaction catalyzed by amyloglucosidase (Bas & Boyaci, 2007). Many of these studies have demonstrated consistently that the predictive capability of ANN is stronger than RSM (Bas & Boyaci, 2007;Betiku & Taiwo, 2015;Emeko et al, 2015).…”
mentioning
confidence: 99%